The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1016/0378-1097(95)00009-t
|View full text |Cite
|
Sign up to set email alerts
|

Gene clusters encoding the cytotoxic necrotizing factor type 1, Prs-fimbriae and α-hemolysin form the pathogenicity island II of the uropathogenic Escherichia coli strain J96

Abstract: The uropathogenic Escherichia coli strain J96 (04:K6) is able to produce four adherence factors [P-fimbriae (pap and prs), F1C-fimbriae (foc) and Type 1-fimbriae (fim)], two alpha-hemolysins (hlyI and II) and the cytotoxic necrotizing factor type 1 (cnf1). Using phenotypic test systems and genotypic analysis, it has been shown that the mutant strain J96-M1 has lost the hlyII, prs and cnf1 genes. The three virulence associated determinants are linked on one particular region on the chromosome, which is termed '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 11 publications
11
133
1
2
Order By: Relevance
“…In a study by Sabate et al, PAI IV536 was found most frequently in both commensal and UPEC isolates from patients with pyelonephritis and urinary sepsis [14]. In most studies worldwide, the presence of PAI IV536 in the Enterobacteriace family is documented, and this marker is known as broad-hostrange PAI or high-pathogenicity island (HPI) [11,18,19]. Our results also showed that one UPEC isolate from patients with an implanted catheter and four UPEC isolates from patients without urinary catheters suffering from sepsis carried only PAI IV536 as a single PAI marker.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sabate et al, PAI IV536 was found most frequently in both commensal and UPEC isolates from patients with pyelonephritis and urinary sepsis [14]. In most studies worldwide, the presence of PAI IV536 in the Enterobacteriace family is documented, and this marker is known as broad-hostrange PAI or high-pathogenicity island (HPI) [11,18,19]. Our results also showed that one UPEC isolate from patients with an implanted catheter and four UPEC isolates from patients without urinary catheters suffering from sepsis carried only PAI IV536 as a single PAI marker.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity-associated islands are common among ExPEC (Blum et al, 1995;Chen et al, 2006;Lloyd et al, 2007) and have some characteristic features, including: (1) disparate G+C content from the core genome; (2) association with pathogenic organisms, but not commensal counterparts; (3) contain virulence-associated genes; (4) insertion sites or flanking direct repeats; (5) a high frequency of insertion at tRNA sites and (6) often mobility (pseudo)genes (Dobrindt et al, 2004;Gal-Mor & Finlay, 2006;Hacker & Kaper, 2000). PAI-X was associated with E. coli isolated from patients experiencing a variety of clinical syndromes, including asymptomatic bacteriuria, cystitis, (Hannan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The pap/prs gene clusters coding for P®mbriae and the cnf1 gene are actually associated with a hly operon coding for the ahemolysin, forming the so-called pathogenicity island 5 or Pai 5 (Blum et al, 1995;De Rycke et al, 1999;Dozois and Curtiss III, 1999).…”
Section: Introductionmentioning
confidence: 99%